Tingkat Fertilitas Telur Ayam Ras Tipe Leghorn Hasil Inseminasi Buatan Menggunakan Pejantan Bangkok - Andika Kurniafajar Putra Pradana; Dirwan Muclis; Nurcholis Nurcholis; Desmina Kirtiani Hutabarat (Faculty of Agriculture, Musamus University, 2022)
This study aims to determine the fertility of broiler chicken eggs crossed with Bangkok roosters, using artificial insemination techniques in broiler broodstock. Chickens used in this study are one male Bangkok chicken and nine broodstocks, then the eggs from the cross were taken and hatched using a semi-automatic hatching machine. The variables observed in this study were egg weight, fertility, hatchability, and hatching weight. The results of this drop are then percentage using an average count and the data obtained will be processed using descriptive analysis. The results of this study showed the fertility results of IB reached 81.48% and the hatchability of 69.23%.